O esporte no capitalismo tardio: Imbricações entre cultura esportiva, economia e mercado - Reis, Nadson Santana (2020)
This text embodies a theoretical and conceptual effort to locate culture - more generally - and sport - more specifically - within the framework of contemporary capitalist production. Therefore, we sought to reflect on the development of culture in the context of late capitalism with attention to the approximation between culture, economy and market. This is done in order to understand the transformations that, in this historical court, go through modern sport. Thus, the considerations point to the processes of integration between market economy and mass culture. This has led, especially in the sports field, to the production of a set of commodities (cultural commodities) that have come to interact with various productive sectors of the capitalist world, which nevertheless need them to make accumulations and generate possible profits.